1993
DOI: 10.1037/0022-0663.85.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Influence of behavior perceptions and gender on teachers' judgments of students' academic skill.

Abstract: This study evaluated the hypothesis that gender and behavior, as perceived by teachers, affect judgments of the academic skills of their students. A path model was proposed to describe the relationships among tested academic skill, gender, behavior grades, and teachers' academic judgments. The model was evaluated separately in each of 3 grades (kindergarten-2nd) in 2 locations, with scholastic grades and structured ratings in specific academic skill areas as the dependent variables. Results showed that, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
2
8

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 22 publications
6
91
2
8
Order By: Relevance
“…This finding may indicate that primary school teachers consider positive working habits and being self-confident as important student attributes for being successful in the higher tracks of Dutch secondary education. On the other hand, teachers appeared to have lower expectations for students whom they perceived as exhibiting more positive social behavior in the classroom, which contradicts findings from previous research (Bennet et al 1993;Hecht and Greenfield 2002;Kelly and Carbonaro 2012;LaVoie and Adams 1973), where it was concluded that teachers on average had higher expectations for students with good conduct. Contrary to our expectations, we did not find evidence for a relationship between teachers' expectations for students' future academic performance and teachers' perceptions of the student-teacher relationship after several performance measures and other perceptions were controlled for.…”
Section: Conclusion and Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This finding may indicate that primary school teachers consider positive working habits and being self-confident as important student attributes for being successful in the higher tracks of Dutch secondary education. On the other hand, teachers appeared to have lower expectations for students whom they perceived as exhibiting more positive social behavior in the classroom, which contradicts findings from previous research (Bennet et al 1993;Hecht and Greenfield 2002;Kelly and Carbonaro 2012;LaVoie and Adams 1973), where it was concluded that teachers on average had higher expectations for students with good conduct. Contrary to our expectations, we did not find evidence for a relationship between teachers' expectations for students' future academic performance and teachers' perceptions of the student-teacher relationship after several performance measures and other perceptions were controlled for.…”
Section: Conclusion and Discussioncontrasting
confidence: 57%
“…Previous findings indicate that teachers do have different perceptions of boys and girls and, on some occasions, this did influence teachers' decisions regarding achievement levels (Riley 2014). Consistent with the current study, female students are generally perceived by their teachers as working harder and producing higher quality work (Bennet et al 1993;Reyna 2000;Siegle and Reis 1994). In the current study we did not have any other objective indicator of the student attributes and classroom behavior, therefore it was not possible to investigate which of the two explanations was the most likely.…”
Section: Conclusion and Discussionsupporting
confidence: 51%
See 3 more Smart Citations